Skin symptoms as diagnostic clue for autoinflammatory diseases - Alvaro Moreira; Barbara Torres; Juliano Peruzzo; Alberto Mota; Kilian Eyerich; Johannes Ring (Anais Brasileiros de Dermatologia, 2017)
ABSTRACT Autoinflammatory disorders are immune-mediated diseases with increased production of inflammatory cytokines and absence of detectable autoantibodies. They course with recurrent episodes of systemic inflammation and fever is the most common symptom. Cutaneous manifestations are prevalent and important to diagnosis and early treatment of the syndromes. The purpose of this review is to emphasize to dermatologists the skin symptoms present in these syndromes in order to provide their early diagnosis.